2017
DOI: 10.1111/jon.12448
|View full text |Cite
|
Sign up to set email alerts
|

Sodium MRI of T1 High Signal Intensity in the Dentate Nucleus due to Gadolinium Deposition in Multiple Sclerosis

Abstract: Normal sodium signal in the T1-hyperintense DN in MS patients may point to relative tissue integrity despite gadolinium deposition in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
(42 reference statements)
1
14
1
1
Order By: Relevance
“…In contrast to previous studies, we did not find any indication of a washout of Gd deposits neither over time [25,26] nor when linear GBCA were followed by cyclic GBCA [13,14,29,30]. Alternatively, Gd washout may follow kinetics not detectable by our study, in which relatively homogenous intervals (about 11 months) were analyzed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies, we did not find any indication of a washout of Gd deposits neither over time [25,26] nor when linear GBCA were followed by cyclic GBCA [13,14,29,30]. Alternatively, Gd washout may follow kinetics not detectable by our study, in which relatively homogenous intervals (about 11 months) were analyzed.…”
Section: Discussioncontrasting
confidence: 99%
“…Maximum intensity projection indicates that no further area was identified (c) sue damage, in MS patients. Within areas of increased T1w signal intensities of the DN, a normal sodium signal was determined and, hence, no evidence of GBCA-related tissue damage provided [30]. In addition, there may be kinetic aspects to be considered for the evaluation of MS patients with respect to Gd deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns over NSF and, more recently, Gd retention have led to a widespread migration from linear GBCAs to macrocyclic GBCAs for routine clinical use. Although studies to date suggest that GBCA exposure has no long‐term detrimental effects on human health either in terms of direct impact on tissue integrity, or global clinical disability, the possibility of long‐term effects is nevertheless a major area of current concern . Although assessment of potential long‐term safety issues was beyond the scope of this observational study, it is worth noting that all studies thus far performed in animals to evaluate Gd retention in brain and body tissues following GBCA exposure have shown that gadoteridol is retained to a lesser extent and cleared more rapidly than other GBCAs, including other macrocyclic GBCAs .…”
Section: Discussionmentioning
confidence: 99%
“…25 These studies failed to demonstrate an association of brain gadolinium deposition with worsening of neurologic or neuropsychological status. 24,25 Also, studies applying imaging techniques to evaluate brain microstructural and functional integrity, such as sodium MR imaging, 26 resting-state functional MR imaging connectivity, 27 and http://dx.doi.org/10.3174/ajnr.A6586…”
Section: Brain Gadolinium Depositionmentioning
confidence: 99%